The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/antiox11020205
|View full text |Cite
|
Sign up to set email alerts
|

Cynanchi atrati and Its Phenolic Constituent Sinapic Acid Target Regulator of Calcineurin 1 (RCAN1) to Control Skin Inflammation

Abstract: Atopic dermatitis (AD) is a common inflammatory skin disorder, and numerous pharmacological approaches are employed to reduce symptoms. Natural products of plant-derived materials have been accepted as complementary therapy for the treatment of a wide range of inflammatory diseases. Cynanchi atrati (CA) is an oriental medicinal herb used in the treatment of acute urinary infection, febrile diseases, and laryngopharyngitis. However, the role of CA root extract in skin inflammation such as AD has not been explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Combining these results, the animal and cell model simulated the process of heart disease caused by hyperthyroidism, which could be applied to investigate the molecular mechanism. As shown in Figure 11 , an increase in Cav1.3 induces an increase in the cytosolic Ca 2+ concentration of H9c2 cells, thereby increasing the activation of Ca 2+ -dependent signalling, Rcan1, calcineurin, and calpain, which subsequently upregulates the gene expression of hypertrophy markers and upregulates the gene expression of inflammatory cytokines by activating the NF-κB/p65-dependent signalling pathway [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], causing cardiac hypertrophy and inflammation. Meanwhile, the elevation of Gal-3, RhoA, and Rock further increased ROS [ 27 , 28 , 29 , 30 , 31 , 32 ], subsequently regulating the Bcl-2/caspase-3-dependent apoptotic signalling pathway [ 33 , 34 ], thereby leading to cell rupture and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Combining these results, the animal and cell model simulated the process of heart disease caused by hyperthyroidism, which could be applied to investigate the molecular mechanism. As shown in Figure 11 , an increase in Cav1.3 induces an increase in the cytosolic Ca 2+ concentration of H9c2 cells, thereby increasing the activation of Ca 2+ -dependent signalling, Rcan1, calcineurin, and calpain, which subsequently upregulates the gene expression of hypertrophy markers and upregulates the gene expression of inflammatory cytokines by activating the NF-κB/p65-dependent signalling pathway [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], causing cardiac hypertrophy and inflammation. Meanwhile, the elevation of Gal-3, RhoA, and Rock further increased ROS [ 27 , 28 , 29 , 30 , 31 , 32 ], subsequently regulating the Bcl-2/caspase-3-dependent apoptotic signalling pathway [ 33 , 34 ], thereby leading to cell rupture and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, more than 400 compounds have been isolated from diverse members of the Asclepiadaceae family, including steroids, acetophenones, saponins, alkaloids, flavonoids, terpenes, polysaccharides, and other compounds [ 18 , 19 , 30 ]. Pharmacological research has revealed that Cynanchum atratum , including its isolated components, possesses anti-inflammatory, cytotoxic, antitumor, and even acetylcholinesterase inhibitory properties [ 14 , 17 ]. Although Cynanchum atratum has been shown to have immunosuppressive effects, it is uncertain whether CF has comparable effects and what its intrinsic molecular mechanisms are.…”
Section: Discussionmentioning
confidence: 99%
“…We found that CF markedly suppressed LPS-induced phosphorylation of MAPKs, such as p38, JNK, and ERK, and subsequent AP-1 transcriptional activation in a dose-dependent manner. In our previous study, crude extracts of Cynanchum atratum and one of the isolated compounds, sinapic acid, exerted an anti-inflammatory function by inhibiting NF-κB signaling [ 17 ]. In addition to this report, our current study suggests that CF suppresses LPS-induced inflammatory signaling by inhibiting the MAPK/AP-1 signaling axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout of the RCAN1 gene can aggravate proteinuria and podocyte injury in mice with adriamycinnephropathy 29 . Recent studies have revealed that RCAN1 can regulate the NF‐κB signalling pathway, thereby participating in the process of skin inflammation 30 . The up‐regulated expression of RCAN1 in vascular endothelial cells can promote the integrity of the vascular endothelial barrier and reduce vascular permeability 31 .…”
Section: Introductionmentioning
confidence: 99%